2020
DOI: 10.3390/brainsci10120930
|View full text |Cite
|
Sign up to set email alerts
|

Covert Cognition in Disorders of Consciousness: A Meta-Analysis

Abstract: Covert cognition in patients with disorders of consciousness represents a real diagnostic conundrum for clinicians. In this meta-analysis, our main objective was to identify clinical and demographic variables that are more likely to be associated with responding to an active paradigm. Among 2018 citations found on PubMed, 60 observational studies were found relevant. Based on the QUADAS-2, 49 studies were considered. Data from 25 publications were extracted and included in the meta-analysis. Most of these stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 48 publications
2
25
2
Order By: Relevance
“…Only a few studies on DoC have collected multimodal clinical and neurophysiological findings in a multicentre longitudinal design [17]. Third, as this study was based on clinical diagnosis and did not have a complete neuroimaging workup, we could not search for signs of covert cognition [49] and analyse mortality in patients showing such signs. Fourth, the multicentre design of the present study made it possible to reduce the sampling biases and idiosyncrasies of single-centre studies, but we could not analyse our data stratified for country, as samples were too small to be representative.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies on DoC have collected multimodal clinical and neurophysiological findings in a multicentre longitudinal design [17]. Third, as this study was based on clinical diagnosis and did not have a complete neuroimaging workup, we could not search for signs of covert cognition [49] and analyse mortality in patients showing such signs. Fourth, the multicentre design of the present study made it possible to reduce the sampling biases and idiosyncrasies of single-centre studies, but we could not analyse our data stratified for country, as samples were too small to be representative.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all patients (n=4) that showed command following in an active functional magnetic resonance imaging (fMRI) task had preserved spindling activity during sleep. As active paradigms have been suggested to aid the diagnosis 49 , sleep spindles might be an interesting marker to take into consideration.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Monti and colleagues in their study found that 10% of the patients that appeared to be vegetative showed signs of awareness and were able to conduct mental imagery tasks in an fMRI scanner ( 9 ). Later, it was argued that 14–17% of patients suffering from PDoC showed brain activity that might account for consciousness when participating in these studies ( 10 , 11 ). Another study demonstrated that also EEG could be used to uncover awareness in patients suffering from VS (which is of significant interest considering the practical and financial advantages of EEG as compared to fMRI) ( 12 ).…”
Section: Disorders Of Consciousness and Neuroimagingmentioning
confidence: 99%